Limpet (Scutellastra cochlear) Recovered From Some Estuaries in the Eastern Cape Province, South Africa Act as Reservoirs of Pathogenic Vibrio Species - Abioye, Oluwatayo E.; Okoh, Anthony I. (Frontiers in Public Health, 2018)
Limpet (Scutellastra cochlear) serves as seafood recipe and an important member of the aquatic food chain. It is an abundant mollusc in some aquatic environment in South Africa. In this study, we investigated the potential of the molluscs harvested from the Buffalo, Swartkops and Kowie estuaries in the Eastern Cape Province, South Africa to serve as transient or maintenance reservoir of Vibrio species. The mollusc and source water samples were collected monthly from the rivers between December 2016 and November 2017. The reservoir category of the limpet samples recovered was determined by employing the combination of MPN-PCR method and statistical analysis (comparison of mean and proportion tests). The densities of Vibrio spp. in limpet and their source water samples were determined using MPN-PCR methods. Presumptive isolates were recovered by processing the samples with thiosulfate-citrate-bile salts-sucrose agar and where necessary, samples were enriched with alkaline peptone water. The presumptive isolates were identified using PCR methods with emphasis on six Vibrio species of public health importance. Vibrio spp. were detected in all the limpet samples but not in all the water samples. The densities of Vibrio spp. in the limpet samples were more than the densities of Vibrio species in their source water and these were significant at P < 0.05. In like manner, five out of the six key Vibrio pathogens targeted in this study were more prevalent in limpet samples than in source water samples. Based on our findings, we concluded that our method though could be improved on, is efficient for the determination of reservoir types of bacterial-carrying organisms. We also concluded that the limpets found in the estuaries are not just a transient but a maintenance reservoir of Vibrio spp. which could cause vibrio-related infections.